PENGARUH PERBANDINGAN JUMLAH INDUK JANTAN DAN BETINA TERHADAP PERFORMA BENIH IKAN TAWES (Barbonymus gonionotus) - Parenrengi Parenrengi; Andi Adam Malik; Rismawaty Rusdi; Yusdalifa Ekayanti Yunus; Yushra Yushra (Universitas Mataram, 2024)
One of the phases that determines the success of fish farming is the egg hatching phase. The production of good quality Tawes larvae can occur if the hatchability of eggs is high and quality of eggs produced is good. The hatchability of eggs is relatively low at only 22% and can only produce approximately 10,000 fry, this is an important problem in the spawning process of Tawes fish in Indonesia. As an effort to increase the hatching rate of Tawes fish eggs, this is by treating the ratio of male to female broodstock differently in each hatching container. This research aims to determine the effect of comparison of the number of male and female broodstock on Tawes fish seed production and to find out how many seeds are produced by the ratio of male and female Tawes fish broodstock. The research was carried out for one month using the experimental design method. The parameters observed were the degree of egg hatching and air quality measurements, then data obtained were analyzed using a Completely Randomized Design (CRD) using SPSS 24 for Windows software. The results of the research showed that the ratio of male to female broodstock had an effect on production of Tawes fish (Barbonymus gonionotus) larvae, where the highest larvae production was obtained at a male broodstock ratio of 2: 1 female.